Alkynyl nicotinamides show antileukemic activity in drug-resistant acute myeloid leukemia - Ramdas, Baskar; Dayal, Neetu; Pandey, Ruchi; Larocque, Elizabeth; Kanumuri, Rahul; Pasupuleti, Santhosh Kumar; Liu, Sheng; Kanellopoulou, Chrysi; Chu, Elizabeth Fei Yin; Mohallem, Rodrigo; Virani, Saniya; Chopra, Gaurav; et al. (The Journal of Clinical Investigation, 2024)
Activating mutations of FLT3 contribute to deregulated hematopoietic stem and progenitor cell (HSC/Ps) growth and survival in patients with acute myeloid leukemia (AML), leading to poor overall survival. AML patients treated with investigational drugs targeting mutant FLT3, including Quizartinib and Crenolanib, develop resistance to these drugs. Development of resistance is largely due to acquisition of cooccurring mutations and activation of additional survival pathways, as well as emergence of additional FLT3 mutations. Despite the high prevalence of FLT3 mutations and their clinical significance in AML, there are few targeted therapeutic options available. We have identified 2 novel nicotinamide-based FLT3 inhibitors (HSN608 and HSN748) that target FLT3 mutations at subnanomolar concentrations and are potently effective against drug-resistant secondary mutations of FLT3. These compounds show antileukemic activity against FLT3ITD in drug-resistant AML, relapsed/refractory AML, and in AML bearing a combination of epigenetic mutations of TET2 along with FLT3ITD. We demonstrate that HSN748 outperformed the FDA-approved FLT3 inhibitor Gilteritinib in terms of inhibitory activity against FLT3ITD in vivo.